Where Does the Predictability from Sorting on Returns of Economically Linked Firms Come From?. (7th December 2021) - Burt, Aaron; Hrdlicka, Christopher
Abstract: Cross-firm predictability among economically linked firms can arise when both firms exhibit their own momentum and their returns are contemporaneously correlated. We show that cross-firm predictability can last up to 10 years, which is hard to reconcile with an interpretation of slow information diffusion. However, it is consistent with the economically linked firms' commonality in momentum. The contribution of each source can be found by decomposing leaders' returns into the predictable (momentum) and news components. Sorting on each, we find that both sources contribute almost equally to 1-month predictability, whereas commonality in momentum is solely responsible for longer-horizon cross-firm predictability.